94 The Effects of Dietary Crude Protein, Acidifier, and Pharmacological Levels of Zinc on Growth Performance of Nursery Pigs. (7th May 2021) - Hutchens, Wade M; Tokach, Mike D; Woodworth, Jason C; DeRouchey, Joel M; Goodband, Robert D; Dritz, Steve S; Calderon, Hilda I
Abstract: Weanling pigs (n = 360, DNA 200 × 400, initially 5.90 kg) were used to evaluate pharmacological levels of Zn (ZnO), diet acidification (sodium diformate; Addcon, Bitterfeld-Wolfen, Germany), and crude protein (18 or 21% CP) on pig performance. At weaning, pigs were assigned to treatments with 5 pigs/pen and 9 pens/treatment. Treatments were arranged in a 2×2×2 factorial with main effects of Zn (110 mg/kg from d 0 to 21 or 3, 000 mg/kg from d 0 to 7, and 2, 000 mg/kg from d 7 to 21), diet acidification (without or with 1.2% sodium diformate), and dietary CP (21 or 18%). The 21% CP diets were formulated to 1.40 and 1.35% SID Lys in phase 1 and 2, respectively, and 18% CP diets were formulated to 1.20% SID Lys. Experimental diets were fed from d 0 to 21 with a common diet from d 21 to 42. Fecal samples were collected weekly to determine fecal dry matter (DM). Data were analyzed using R Studio as a RCBD. From d 0 to 21, ADG and G:F increased (P < 0.05) for pigs fed pharmacological Zn, and sodium diformate. Overall, ADG tended (P ≤ 0.069) to increase for pigs fed added Zn or sodium diformate. Pigs fed 21% CP had increased (P < 0.05) ADG and G:F from d 0 to 21 and overall G:F compared with those fed 18% CP. Feeding 18% CP diets increased fecal dry matter on d 7 when pharmacological Zn and sodium diformate were not in the diet (Zn×acidifier×CP interaction, P < 0.05). From d 21 to 42, there was no evidence of difference in growth performance. In conclusion, reducing CP without acidification increased fecal DM when pharmacological Zn were not in the diet, but had little effect when it was in the diet. Adding sodium diformate and pharmacological Zn independently improved nursery pig growth performance.